Comparison of surgical outcomes between 3-dimensional and 2-dimensional laparoscopy of ovarian cyst (LOOC): a randomised controlled trial. (4th July 2022) - Han, Young Gi; Lim, Kyung Min; Song, Taejong
Abstract: The purpose of this study was to compare the surgical outcomes and efficacy of 3-dimensional (3D) versus 2-dimensional (2D) imaging systems for the treatment of ovarian cyst. A total of 46 patients undergoing a laparoscopic ovarian cystectomy were randomly assigned to either the 3D or 2D laparoscopy group. The primary outcome measure was the operative blood loss. The secondary outcome measure was visually induced motion sickness (VIMS), task efficacy during laparoscopy, and postoperative complication. There were no differences in baseline demographics between the two groups. The operative blood loss was significantly smaller in the 3D groups (28.7 ± 11.6 mL) than in the 2D groups (46.5 ± 24.4 mL) ( p = .012). VIMS score was significantly higher in the 3D groups than the 2D groups ( p < .001). 3D laparoscopy was superior to 2D in terms of the task efficacy of ovarian cyst enucleation ( p < .001), adhesiolysis or dissection ( p < .001), and ovarian suturing ( p = .008). None of the patients in both groups developed operative complications. In conclusion, a 3D imaging system showed a more favourable surgical outcome and improved task efficacy than 2D in laparoscopic ovarian cystectomy. However, 3D laparoscopy tends to cause more frequent VIMS in surgeons. Impact statement: What is already known on this subject? Several studies examining the possible benefits and drawbacks of a 3D imaging system versus 2D in laparoscopic surgery have brought about conflicting results. However, there have been few studies comparing the surgical outcomes of 3D and 2D laparoscopic ovarian cystectomy. What do the results of this study add? 3D laparoscopy showed favourable surgical outcomes and improved task efficacy than 2D laparoscopy in ovarian cystectomy. What are the implications of these findings for clinical practice and/or further research? More complex procedures, such as suturing and adhesiolysis, might be easier to perform with 3D laparoscopy than with 2D laparoscopy. Therefore, further large studies of 3D gynaecologic laparoscopy with different complexities and for surgeons with different surgical skills are needed.